Between Identity and Interest: Revisiting Sharia Bylaw in Current Indonesia - Endi Aulia Garadian (Studia Islamika, 2016)
The emergence of sharia bylaws in several regions in Indonesia is increasingly worrisome. In many cases, they have generated socio-religious problems within society such as preventing the establishment of a house of worship and forbidding of religious activities, especially for minority sects such as Ahmadiyya and Shi’a. Furthermore, they also produce the discrimination against women. For example, in Tangerang City, a female worker was arrested by Civil Service Police Unit (Satuan Polisi Pamong Praja, Satpol PP) because she was accused of being prostitute because she returned home at night. Unfortunately, the basis of accusation is Perda Kota Tangerang No. 5, 2005.One of the prominent factors giving occasion to the emergence of those sharia bylaws is the political opportunity after the decline of Suharto’s New Order. Afterwards, the falling regime became a sign of this glitch. Ignoring the fact that they produce many problems within society, local governments still repeatedly produce sharia bylaws.DOI: 10.15408/sdi.v23i2.3672